Clinical evaluation of efficacy, tolerability and pharmacokinetics of yimitasvir phosphate in patients infected with hepatitis C virus. (6th April 2018) - Zhang, Hong; Zhu, Xiaoxue; Li, Qingmei; Lou, Jinfeng; Sun, Jixuan; Shen, Zhenwei; Chen, Hong; Li, Xiaojiao; Wu, Min; Li, Cuiyun; Liu, Jingrui; Liu, Chengjiao; et al.
Abstract: Objective: Yimitasvir phosphate, an inhibitor of nonstructural protein 5A (NS5A) replication complex of hepatitis C virus (HCV), was evaluated in a double-blind, placebo-controlled, parallel, multiple-dose study. Methods: Twenty-four patients with chronic HCV genotype 1 infection were randomized to receive a 7-day course of yimitasvir phosphate at daily doses of 30, 100 or 200 mg or placebo. Antiviral efficacy, resistance profile, pharmacokinetics (PK), safety and tolerability were assessed. Key findings: The maximal reduction in HCV RNA from baseline was 5.17 log10 IU/ml. However, most patients experienced viral rebound on or before day 3 after yimitasvir treatment was initiated. The PK profile revealed median peak plasma concentrations at 4–12 h postdose and a mean terminal half-life of 14.47–17.09 h, the basis for daily dosing. Steady drug state was achieved following 5 days of daily dosing. The accumulation rate was low (1.29–1.73). There were no significant alterations in vital signs and laboratory findings among all participants. Conclusions: This study shows that yimitasvir phosphate was well tolerated, and the PK profile supported daily dosing regimens. A 1-week (7-day) treatment course led to a quick and significant reduction in HCV RNA level in this cohort with HCV GT-1 infection.